Conspiracy Theories: Plagues in Antiquity and the Ebola Virus Disease in Africa (2015)
Conspiracy theory is the belief that a tactically employed plot by superior instigators and adherents o f a faction is utilized to dethrone any imagined or real opposition thereby achieving an evil end Several scholars have attempted to interrogate conspiracy theories and its appeal in given societies. Others note that conspiracy theories which were once limited to fringe audiences, have become prevalent in mass media and consequently, emerging as a cultural phenomenon around the world today. The aim of this study is to examine conspiracy theories in the light o f the plagues or epidemics that devastated people in antiquity and the ebola virus disease in Africa, with a view to intrinsically interrogating the relevance of conspiracy theories to the growth and development o f society. This study puts forward the argument that society becomes more aware and protective o f herself when she assumes that a form o f conspiracy is being strategized, advertently or inadvertently, by a superior power to completely disable and decimate her bourgeoning population. The study adopts the historical and comparative enquiry approaches in examining the phenomenon with regard to the diseases in both societies. Critical theory is adopted as theoretical framework for the study